Multi-Objective Optimization for Energy, Comfort, and Daylighting in High-Rise Residential Buildings - Hao, Zhe (Scientific Journal of Technology, 2025)
This study addresses the multi-objective conflicts in daylighting, thermal comfort, and energy efficiency inherent in balcony design for high-rise residential buildings. A climate-responsive synergistic optimization framework is proposed, integrating parametric modeling and multi-objective genetic algorithms to systematically analyze the coupled effects of balcony design parameters—including window-to-wall ratio (WWR), shading depth, and thermal properties of building envelopes—across diverse climatic zones (cold, tropical, and hot-summer/cold-winter regions). Key findings reveal: In cold regions (e.g., Xining), enhanced insulation (U ≤ 0.35 W/m²K) is critical, with glazed door width (ST = 0.61) dominating heat gain/loss balance. Tropical regions (e.g., Singapore) require synergistic shading depth (ST = 0.58) and ventilation; 0.5m horizontal overhangs with vertical louvers reduce radiant heat gain by 34%. Adjustable shading components in hot-summer/cold-winter zones (e.g., Changsha) reduce annual severe overheating hours (sGA) by 65% while maintaining daylight sufficiency (sDA ≥ 55%), demonstrating feasible tri-performance synergy (thermal-daylight-energy). A rapid assessment tool integrating Building Information Modeling (BIM) and machine learning algorithms is developed, providing theoretical and practical pathways for low-carbon retrofits in high-density urban residential contexts.